Immunometabolism-fit: How exercise and training can modify T cell and macrophage metabolism in health and disease - Rosa-Neto, José Cesar; Lira, Fábio Santos [UNESP]; Little, Jonathan Peter; Landells, Graham; Islam, Hashim; Chazaud, Bénédicte; Pyne, David B.; Teixeira, Ana Maria; Batatinha, Helena; Moura Antunes, Barbara [UNESP]; Guerra Minuzzi, Luciele [UNESP]; Palmowski, Jana; et al. (My University, 2022)
BACKGROUND: The term immunometabolism describes cellular and molecular metabolic processes that control the immune system and the associated immune responses. Acute exercise and regular physical activity have a substantial influence on the metabolism and the immune system, so that both processes are closely associated and influence each other bidirectionally. SCOPE OF REVIEW: We limit the review here to focus on metabolic phenotypes and metabolic plasticity of T cells and macrophages to describe the complex role of acute exercise stress and regular physical activity on these cell types. The metabolic and immunological consequences of the social problem of inactivity and how, conversely, an active lifestyle can break this vicious circle, are then described. Finally, these aspects are evaluated against the background of an aging society. MAJOR CONCLUSIONS: T cells and macrophages show high sensitivity to changes in their metabolic environment, which indirectly or directly affects their central functions. Physical activity and sedentary behaviour have an important influence on metabolic status, thereby modifying immune cell phenotypes and influencing immunological plasticity. A detailed understanding of the interactions between acute and chronic physical activity, sedentary behaviour, and the metabolic status of immune cells, can help to target the dysregulated immune system of people who live in a much too inactive society.
Keywords: Exercise; Immune System; Inflammation; Metabolism; Sedentary behavior